Noise vs. news in equity returns - Robert S. Chirinko; Hisham Foad (Center for Economic Studies and ifo Institute (CESifo), 2006)
What role does noise play in equity markets? Answering this question usually leads immediately to specifying a model of fundamentals and hence the pervasive joint hypothesis quagmire. We avoid this dilemma by measuring noise volatility directly by focusing on the behavior of country closed-end funds (CCEF's) during foreign (i.e., non-U.S.) holidays - for example, the last days of Ramadan in Islamic countries. These holiday periods are times when the flow of fundamental information relevant to foreign equity markets is substantially reduced and hence trading of CCEF's in U.S. markets can be responding only weakly, if at all, to fundamental information. We find that, controlling for the effects of industry and global shocks and of the overall U.S. market, there remains a substantial amount of noise in the equity returns of U.S. CCEF's. In the absence of noise, the noise ratio statistic would be near zero. However, our results indicate statistically significant departures from zero, with values averaged over all U.S. CCEF's ranging from 76-84% depending on assumptions about the leakage of information during holiday periods and kurtosis. Noise is negatively related to institutional ownership of U.S. CCEF's and is much less important for U.K. CCEF's. The lower levels of noise for matched U.K. and U.S. CCEF's suggest that the U.K. securities transaction tax is effective in reducing stock market noise.
Keywords: G1; G14; G18; 330